A direct transform for determining the trapped mass on an internal combustion engine based on the in-cylinder pressure resonance phenomenon. (October 2015) - Broatch, Alberto; Guardiola, Carlos; Pla, Benjamín; Bares, Pau
Abstract: It has lately been demonstrated that the resonance of the in-cylinder pressure may be used for inferring the trapped mass in an internal combustion engine. The resonance frequency changes over time as the expansion stroke takes place, and hence time–frequency analysis techniques may be used for determining the instantaneous frequency. However, time–frequency analysis has different problems when obtaining the spectral content of the signal, e.g. Short-Time Fourier Transform dilutes the frequency spectrum, and the Wigner Distribution creates cross terms that difficult its interpretation. In addition, time–frequency analysis requires a significant computational burden. This paper presents a direct transform, based on the resonance phenomenon, which obtains the trapped mass by convolving the pressure trace with the theoretical resonance behaviour. The method permits avoiding the spectral problems of the time–frequency transformations by obtaining the trapped mass directly without the need of inferring the frequency content. Abstract : Highlights: The few signals used ensure obtaining small sensor errors at the final measure. The method developed permits one cycle resolution without flow assumptions. The direct transformation reduces the problem to one dimension. The method is not affected by time–frequency analysis complications.